The Effectiveness of the Brute Force Algorithm for Passwords Recovery (International Journal of Psychosocial Rehabilitation, 2020)
Security problems, password theft, phishing websites, crackers, hacking threaten information ownership. Moreover, passwords with minimal durability which is considered as weak passwords become easy targets for crackers. There are so many method used to break the password for recovery lost. Every method has advantage and disadvantage, which is depend on condition and situation, including the characteristic of the password which is need to recover. Brute force is one of the oldest method to recover password, and still be used to recover the password for specific needs. In this research, the Brute Force method will be introduced as a method of recovering and breaking passwords. This method is easy to use in guessing passwords even though it takes longer because it is done by tapping a number of keywords. Thus computer users are more concerned about maintaining the confidentiality of passwords so as not to be easily broken down by others, because with a short time the password can be broken.